The Implementation of Recruitment and Selection Process in Richemont - Sheila Alfauziah Putri; Andriyastuti Suratman; Majang Palupi (PT Mattawang Mediatama Solution, 2023)
Richemont B.V. is a company that owns the prestigious Maisons well-known for its excellence in the luxury industry which includes jewelry, specialist watchmakers, online distributors, and fashion & accessories. This research aims to provide information on the organizational structure of the company and provide a perspective that can build an organization in carrying out better accountability processes and internal communications and dissect the problems faced regarding recruitment and selection. The data collection methods used are observation and interviews. Sources for interviews were chosen to obtain a perspective from the recruiter and non-recruiter parties. The results indicate that major changes in the organizational structure affect the process of communication in the ongoing recruitment and selection, there are challenges in terms of internal communication between the recruitment team and how this internal communication can affect communication with candidates. The research results also reveal the implementation of organizational structure in the recruitment team and provide information related to how the recruitment process is carried out from all aspects